Systematic Review of Strategic Business Administration Practices for Driving Operational Excellence in IT-Driven Firms (International Journal of Scientific Research in Science and Technology, 2024)
This systematic review explores strategic business administration practices that drive operational excellence in IT-driven firms, which are increasingly pivotal in today’s competitive and technology-driven global marketplace. The review synthesizes findings from diverse sources, including academic literature, industry reports, and case studies, to examine how business administration strategies contribute to achieving operational efficiency, innovation, and sustainable growth in IT firms. Operational excellence, defined as the execution of business strategies effectively and efficiently, is crucial for IT firms to maintain competitive advantage, optimize resources, and adapt to rapidly changing technological landscapes. The review identifies key strategic practices, including effective leadership and management, process optimization techniques, and the integration of emerging technologies, as critical drivers of operational excellence. It highlights the role of leadership in shaping organizational culture and aligning business strategies with operational goals. Furthermore, it explores the adoption of technologies such as cloud computing, artificial intelligence, and automation, and their impact on streamlining business processes, improving productivity, and fostering continuous improvement. Challenges to operational excellence, such as resistance to change, market volatility, and regulatory compliance, are also discussed. The review provides valuable insights into best practices and successful case studies from IT-driven firms that have effectively implemented strategic business practices to drive operational excellence. It concludes by offering practical recommendations for IT firms aiming to improve operational performance and maintain long-term success. Additionally, the review identifies gaps in the current literature and suggests areas for future research, particularly in the evolving landscape of digital transformation and strategic business practices in IT industries. The findings emphasize the critical importance of aligning business administration practices with operational goals to achieve sustained success in the dynamic IT sector.